1994
DOI: 10.1073/pnas.91.6.2156
|View full text |Cite
|
Sign up to set email alerts
|

Detection and mapping of amplified DNA sequences in breast cancer by comparative genomic hybridization.

Abstract: Comparative genomic hybridization was applied to 5 breast cancer cell lHes and 33 primary tumors to discover and map regions of the genome with increased DNAsequence copy-number. Two-thirds of primary tumors and almost all cell lines showed increased DNA-sequence copynumber affecting a total of 26 chromosomal subregions. Most of these loci were distinct from those of currently known amplified genes in breast cancer, with sequences originating from 17q22-q24 and 20q13 showing the highest frequency of amplificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

35
433
7
5

Year Published

1998
1998
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 649 publications
(480 citation statements)
references
References 20 publications
35
433
7
5
Order By: Relevance
“…Thus, it would be of interest to know whether a simultaneous It remains to be determined whether there is an oncogene within the 17q23 breast cancer amplicon whose overexpression could drive tumorigenesis in transgenic mice. The 17q23 amplification occurs fairly frequently (B18%) in primary human breast cancers (Kallioniemi et al, 1994;Sinclair et al, 2003) and there are three potential oncogenes, RPS6KB1, TBX-2 and WIP1, which have been identified within this genomic locus (Sinclair et al, 2003). However, overexpression of either WIP1, Tbx2 or both in MMTVtransgenic mice is not sufficient for tumor formation (present study and data not shown).…”
mentioning
confidence: 48%
See 1 more Smart Citation
“…Thus, it would be of interest to know whether a simultaneous It remains to be determined whether there is an oncogene within the 17q23 breast cancer amplicon whose overexpression could drive tumorigenesis in transgenic mice. The 17q23 amplification occurs fairly frequently (B18%) in primary human breast cancers (Kallioniemi et al, 1994;Sinclair et al, 2003) and there are three potential oncogenes, RPS6KB1, TBX-2 and WIP1, which have been identified within this genomic locus (Sinclair et al, 2003). However, overexpression of either WIP1, Tbx2 or both in MMTVtransgenic mice is not sufficient for tumor formation (present study and data not shown).…”
mentioning
confidence: 48%
“…This site has been found to be a hot spot for gene amplifications in multiple types of human cancer. The initial observation of regional gain at chromosome 17q22-23 using a comparative genomic hybridization (CGH) technique detected amplification in B18% of primary breast tumors (Kallioniemi et al, 1994), giving its name to the locus as the 17q23 breast cancer amplicon. Three potential oncogenes, RPS6KB1, TBX-2 and WIP1 have been found within this genomic locus at chromosome 17q22-23 (Sinclair et al, 2003).…”
mentioning
confidence: 99%
“…Inhibition of differentiation would be a prerequisite for the maintenance of proliferative capacity of immortalized cells; (iii) CROC1/UEV-1 maps to chromosome 20q13.2 (Sancho et al, 1998), a region which is moderately ampliÂźed in many types of cancer (e.g. Kallioniemi et al, 1994;Muleris et al, 1994;Tanner et al, , 1995Brinkman et al, 1996) and highly ampliÂźed in others, e.g. breast cancer, where it correlates with aggressiveness and poor prognosis (Tanner et al, 1995).…”
Section: Expression Of Cir1/croc1 In Human Tissues and Tumor-derived mentioning
confidence: 99%
“…The relatively low CGH concordances and correlations involving 19q alterations resulted, in part, from using microsatellite markers and FISH probes that map to 19q13.3, a region in human gliomas that often contains deletions below the resolution of CGH. Furthermore, CGH has known artifacts at both 1p and 19q (Kallioniemi et al, 1994;Kim et al, 1995;Mohapatra et al, 1995).…”
mentioning
confidence: 99%